A Study of Islamic Religious Education Research Methodology from the Perspective of Karl Popper’s Epistemology - Hayat, Ade Putra; Ahida, Ridha; Mukhtar, Dertha (The Future of Education Journal, 2025)
This study analyzes the research methodology of Islamic Religious Education (PAI) from the epistemological perspective of Karl R. Popper, particularly the principle of falsification, to develop critical rationalism. The findings show that integrating falsification into PAI research can enhance scientific validity through critique, hypothesis testing, and continuous theory improvement, enabling Islamic education scholarship not only to legitimize religious values but also to develop them scientifically. The implications of this study include the need to reformulate PAI research methodology, strengthen curricula based on critical epistemology, and foster an academic culture that is open to correction positioning Popper’s epistemology as a bridge between Western scientific traditions and Islamic spirituality for the advancement of progressive and contextual Islamic education.